Uso de L-PRF en defectos infraóseos de pacientes con estadios avanzados de periodontitis - Mera, Stefany (2023)
Objective: The purpose of this study was to observe the effect of L-PRF (Leukocyte-Platelet Rich Fibrin) usage in intraosseous defects in patients with advanced-stages of periodontitis. Methods: Thirty-two intraosseous defects in 12 patients diagnosed with stage III and IV periodontitis (Workshop 2018) were included in the study. Open flap debridement was performed with the placement of L-PRF membranes. Included defects consisted of 1-2-3 wall defects and osseous craters. Parameters such as probing depth (PD), clinical attachment level (CAL), plaque index (PI), and bleeding index (BI) were recorded. Digital periapical radiographs were taken before surgery and at the fourth month to assess bone fill. Results: Out of the 32 defects, 75% showed a reduction in probing depth (PD), and 66% showed improvement in clinical attachment level (CAL). Pre- and post-surgical correlation analysis was performed for PD: MV (p = 0.02), PI/L (p = 0.00), BI/L (p = 0.00), and CAL (p = 0.00). The percentage of bone fill was 62.96% (±3.88 SD). Conclusion: The majority of intraosseous defects exhibited partial or complete radiographic bone fill with the use of L-PRF membranes. Furthermore, clinical parameters such as probing depth and clinical attachment level improved.